New View on the Genesis of the Bashuihe Pluton, Laoshan Granites, China: Indications from Fluid Inclusions and H–O Isotopes. (8th February 2021) - Liu, Huimin; Song, Zhaojun; Yan, Hongbo; Wang, Wenyu; Wang, Xinru; Sun, Yifang; Li, Haonan
Abstract : Oval caves have recently been discovered in the Bashuihe granite pluton of Laoshan Mountain, China. Oval caves typically occur in alkaline granites. This study conducted microthermometry and stable isotope analysis of quartz inclusions from oval caves and host rocks from the Bashuihe pluton to reconstruct the diagenetic evolutionary history of the Laoshan area. The temperature measurement results indicated a homogenisation temperature range from 162.5 to 261.6°C (mean 203.9°C), a salinity range of 2.1–8.3 wt% (mean 5.07 wt%), and a density range of 0.8–0.98 g/cm 3 (mean 0.90 g/cm 3 ), indicating a low-temperature, low-salinity, and low-density fluid. The emplacement depth ranged from 2.73 km to 4.43 km, indicating medium-shallow granite. A hydrogen and oxygen isotope analysis (δ D = − 83.58 – − 67.17, δ 18 O H 2 O = 0.83 – 0.39 ) revealed that the diagenetic fluids of the Bashuihe pluton represented a mixed hydrothermal solution composed of meteoric water and magmatic water. The results of a whole rock, H–O isotopes, rare earth element, and high field strength element analysis on the Laoshan alkali granites suggest significant hydrothermal activity in the late stage of magmatism. Primary oval caves in the Bashuihe pluton most likely evolved in the following sequence: fluid was enriched in the late diagenetic stage, diagenetic minerals crystallised under low temperature and pressure conditions, the crystallisation rate accelerated, and the magma condensed rapidly. Moreover, the increase in magma fluid enabled the movement and convergence of fluid. The accumulated fluid and volatiles occupied more space, and rapid magma condensation trapped the accumulated fluid and volatiles in the pluton, forming the oval granite cave. This research provides a crucial theoretical reference for the development and utilisation of underground space and engineering buildings in granite regions.